Pemanfaatan Ekstrak dan Serbuk Kulit Jeruk Bali (Citrus Maxima Merr) untuk Mereduksi Kadar Krom(VI) dan Kadmium(II) pada Limbah Cair Artifisial - Maria Fransiska Utami Bugis; Nur Hidayati; Dian Kresnadipayana (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
Artificial waste is made using chrome K2Cr2O7 crystals, and cadmium from CdCl2 crystals. The purpose of this study was to determine the utilization of grapefruit skin extracts and powders in reducing the levels of chromium and cadmium. This research was carried out using artificial waste mixed with grapefruit peel extract and powder with a concentration of 0%, 0.5%, 1%, 1.5% and 2%. Metal content was measured using the Atomic Absorption Spectrophotometry method.The results of the research on chromium content before the treatment were 46.49 ppm and after the treatment using powder levels with a concentration of 0.5%; 1%; 1.5% and 2%, are namely 29.97 ppm, 33.20 ppm, 31.05 ppm, and 33.76 ppm, while the levels of extract are 40.43 ppm, 41.94 ppm, 42.34 ppm and 48 , 23 ppm. The results of the study of cadmium metal content before treatment were 102.36 ppm and after treatment using powder levels with variations in concentration of 0.5 %%; 1%; 1.5% and 2%, namely 33.61 ppm, 20.26 ppm, 13.44 ppm, and 16.82 ppm, while the extracts are 75.45 ppm, 74.86 ppm, 80.66 ppm and 85 , 10 ppm.